Fangchinoline induces antiviral response by suppressing STING degradation - Jinyong Wang; Fang Xie; Xin Jia; Xuejiao Wang; Lingdong Kong; Yiying Li; Xue Liang; Meiqi Zhang; Yuting He; Wandi Feng; Tong Luo; Yao Wang; et al. (Elsevier, 2024)
The stimulator of interferon genes (STING), an integral adaptor protein in the DNA-sensing pathway, plays a pivotal role in the innate immune response against infections. Additionally, it presents a valuable therapeutic target for infectious diseases and cancer. We observed that fangchinoline (Fan), a bis-benzylisoquinoline alkaloid (BBA), effectively impedes the replication of vesicular stomatitis virus (VSV), encephalomyocarditis virus (EMCV), influenza A virus (H1N1), and herpes simplex virus-1 (HSV-1) in vitro. Fan treatment significantly reduced the viral load, attenuated tissue inflammation, and improved survival in a viral sepsis mouse model. Mechanistically, Fan activates the antiviral response in a STING-dependent manner, leading to increased expression of interferon (IFN) and interferon-stimulated genes (ISGs) for potent antiviral effects in vivo and in vitro. Notably, Fan interacts with STING, preventing its degradation and thereby extending the activation of IFN-based antiviral responses. Collectively, our findings highlight the potential of Fan, which elicits antiviral immunity by suppressing STING degradation, as a promising candidate for antiviral therapy.